Practice variation in anastomotic leak after esophagectomy: Unravelling differences in failure to rescue. Issue 5 (May 2023) - Ubels, Sander; Matthée, Eric; Verstegen, Moniek; Klarenbeek, Bastiaan; Bouwense, Stefan; van Berge Henegouwen, Mark I.; Daams, Freek; Dekker, Jan Willem T.; van Det, Marc J.; van Esser, Stijn; Griffiths, Ewen A.; Haveman, Jan Willem; et al.
Abstract: Introduction: Failure to rescue (FTR) is an important outcome measure after esophagectomy and reflects mortality after postoperative complications. Differences in FTR have been associated with hospital resection volume. However, insight into how centers manage complications and achieve their outcomes is lacking. Anastomotic leak (AL) is a main contributor to FTR. This study aimed to assess differences in FTR after AL between centers, and to identify factors that explain these differences. Methods: TENTACLE – Esophagus is a multicenter, retrospective cohort study, which included 1509 patients with AL after esophagectomy. Differences in FTR were assessed between low-volume (<20 resections), middle-volume (20–60 resections) and high-volume centers (≥60 resections). Mediation analysis was performed using logistic regression, including possible mediators for FTR: case-mix, hospital resources, leak severity and treatment. Results: FTR after AL was 11.7%. After adjustment for confounders, FTR was lower in high-volume vs. low-volume (OR 0.44, 95%CI 0.2–0.8), but not versus middle-volume centers (OR 0.67, 95%CI 0.5–1.0). After mediation analysis, differences in FTR were found to be explained by lower leak severity, lower secondary ICU readmission rate and higher availability of therapeutic modalities in high-volume centers. No statistically significant direct effect of hospital volume was found: high-volume vs. low-volume 0.86 (95%CI 0.4–1.7), high-volume vs. middle-volume OR 0.86 (95%CI 0.5–1.4). Conclusion: Lower FTR in high-volume compared with low-volume centers was explained by lower leak severity, less secondary ICU readmissions and higher availability of therapeutic modalities. To reduce FTR after AL, future studies should investigate effective strategies to reduce leak severity and prevent secondary ICU readmission.